Parallel Connected VSI Inverter using Multi-carrier based Sinusoidal PWM Technique - D. Karthikeyan; R. Palanisamy; K. Vijayakumar; A. Velu; D. Selvabharathi (Universitas Ahmad Dahlan, 2017)
This paper explains the simulation and modelling of Parallel operation of VSI inverter using multi-carrier based PWM technique. By this proposed method three level inverter output voltages generated instead of using multilevel inverter or two level dual VSI inverter. This system employs single dc voltage source, which gives supply to both VSI inverter by using parallel connection. The multi-carrier based pulse width modulation technique affianced to control the inverter power switches. The proposed system offers improved output voltage, better current control and reduced harmonic distortion. The simulation results of this proposed system was verified using matlab/simulink.